TECHNICAL AND ECONOMIC EVALUATION OF MINERAL FILLER APPLICATION IN POLYETHYLENE FILM PRODUCTION - БУЛГАКОВ, Є. С.; РОЗВОРА, Л. В.; САВЧЕНКО, Б. М.; СОВА, Н. В.; СЛЄПЦОВ, О. О. (Technologies and Engineering, 2025)
Purpose. The purpose of this article is to make assessment of the raw material composition cost for polyethylene film with calcium carbonate base filler. Methodology. The density of the film samples was determined according to ISO 1183 by hydrostatic weighing. The volume and mass cost of the film composition was determined by the calculation formulas. Blown film with different filler content was obtained on laboratory extrusion equipment. The strength and relative elongation at break for the tested samples were determined according to ISO 527. Findings. The methods of modifying polymeric materials by introducing various additives that can regulate the properties of final products are analyzed. The possibilities of using calcium carbonate as a modifier of the properties of polyethylene films, in particular, to regulate the density of final products and reduce their cost, are considered. Low-density polyethylene films of the Sabic LDPE HP2023J brand with different content of calcium carbonate filler were obtained using Omya AG’s Omyalene 2021 concentrate containing 70% filler. The film blow-up coefficient was 2.5, and the longitudinal stretching coefficient was 4.5. The density of the obtained films was calculated by the additive method and the measured by hydrostatic weighting method. It was found that calcium carbonate filler content 16% causes a decrease in film density by 8.6% comparing to calculated value, which is probably due to the cavitation or interface effect. The volume cost of the composition containing 40% of the filler is 2.5% lower than the cost of the original low-density polyethylene, which makes it possible to effectively use calcium carbonate as a filler to reduce the cost of film compositions. The introduction of up to 30% of filler allows maintaining the level of mechanical properties suitable for the industrial us of polyethylene films, with corresponding density increases. Originality. The effect of a filler based on calcium carbonate on the mechanical properties of a low-density polyethylene film was determined. Practical value. The limits of the rational content of the filler when applying the cost calculation to the unit volume of the finished product are established.